Jubal Anderson Early papers - Early, Jubal Anderson, 1816-1894.
Correspondence, diaries (1847 February-May and 1865 May-November), speeches, articles, military papers, clippings, scrapbook (1833-1930), printed matter, and maps. The pre-Civil War papers reflect Early's years as a West Point cadet and his U.S. Army service, his law practice, and his Virginia political activities. Includes letters (1829-1833) from John J. Cabell to his wife, Henry Ann Cabell.
Civil War material documents Early's participation in battles at Bull Run (1861) and Williamsburg, Va., and the Gettysburg and Shenandoah Valley campaigns and includes his account of the Confederate advance toward Washington, D.C., in July 1864, Also included are a report on the performance of Isaac Trimble's brigade in the battle of Bull Run (1862), reports by Harry T. Hays and Clement A. Evans on skirmishes in the Mine Run Campaign, a list of units in G.T. Beauregard's I Corps of the Army of Northern Virginia (1862), and a return of troops commanded by Joseph E. Johnston in the spring of 1862.
Postwar material, comprising the bulk of the collection, relates to Early's business affairs, especially the Louisiana lottery, his activities in the Southern Historical Society, and aid extended by Early to Confederate families, including that of Jefferson Davis. Correspondents include G.T. Beauregard, Raleigh Edward Colston, John W. Daniel, Jefferson Davis, Varina Davis, Daniel Harvey Hill, Stonewall Jackson, Bradley T. Johnson, Joseph E. Johnston, Fitzhugh Lee, Robert E. Lee, Dabney Herndon Maury, John Singleton Mosby, and Earl Van Dorn.
Microfilm edition of selections, 1838-1870, available
Microfilm produced from originals in private hands (photostats in the Manuscript Division).
Library of Congress Geography and Map Division.
U.S. and Confederate Army officer, lawyer, and state legislator of Virginia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beauregard, G. T. -- 1818-1893.; Beauregard, G. T. -- 1818-1893 -- Correspondence; Cabell, John J. -- Correspondence; Cabell, Henry Ann -- Correspondence; Colston, Raleigh Edward, -- 1825-1896. -- Correspondence; Daniel, John W. -- 1842-1910 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Family; Evans, Clement A. -- 1833-1911.; Hays, Harry T. -- 1820-1876.; Hill, D. H. -- 1821-1889 -- Correspondence; Jackson, Stonewall, -- 1824-1863 -- Correspondence; Johnson, Bradley T. -- 1829-1903 -- Correspondence; Johnston, Joseph E. -- 1807-1891 -- Correspondence; Lee, Fitzhugh, -- 1835-1905 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Maury, Dabney Herndon, -- 1822-1900 -- Correspondence; Mosby, John Singleton, -- 1833-1916 -- Correspondence; Trimble, Isaac, -- 1802-1888; Van Dorn, Earl, -- 1820-1863 -- Correspondence; Confederate States of America. -- Army -- Officers; Confederate States of America. -- Army of Northern Virginia; Southern Historical Society; United States. -- Army -- Officers; United States Military Academy; Bull Run, 1st Battle of, Va., 1861.; Bull Run, 2nd Battle of, Va., 1862.; Gettysburg Campaign, 1863.; Lotteries -- Louisiana; Mine Run Campaign, Va., 1863.; Practice of law -- Virginia; Reconstruction (U.S. history, 1865-1877); Shenandoah Valley Campaign, 1862.; Williamsburg, Battle of, Williamsburg, Va., 1862.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- Politics and government; Washington (D.C.) -- History -- Civil War, 1861-1865.; Army officers, Confederate; Lawyers; Legislators -- Virginia